Size distribution of brake wear particulate matter based on a brake dynamometer investigation - Zhong, Chongzhi; Sun, Jiaxing; Liu, Zishu; Niu, Haomiao; Zhang, Jing; Liang, Xiaoyu; Yin, Jiawei; Wu, Lin; Peng, Jianfei; Zhang, Qijun; Mao, Hongjun (Frontiers in Future Transportation, 2024)
A brake dynamometer has been modified to accurately study the concentration and size distribution of wear particles in different testing conditions. The test equipment was a charged lowpressure impactor ELPI+ from Dekati, Finland. 29 test conditions were defined based on speed, acceleration and initial brake temperature. Additionally, five different types of brake pads were selected for testing to provide a more comprehensive understanding of the particle size distribution characteristics of brake wear particlesFive different types of brake pads were selected for testing. The results showed that the mass of BWPs was unimodal in the range of 0.01-8.11 μm, with peak sizes at 2-5 μm or >8.11 μm, and particles of 0.5-3.0 μm accounted for an average of 49.09% of the total particulate mass, while particles with sizes of 3.0-8.11 μm accounted for an average of 49.72% of the total particulate mass. The number of particles emitted by abrasion had a bimodal distribution, with one in the nucleation mode and the other in the accumulation mode, with peak sizes of <10 nm and 1 μm, respectively; the nucleation mode particles accounted for an average of 60.11% of the total PN10, and the ultrafine particles accounted for an average of 82.15%.